Analisis Laporan Keuangan yang Sesuai dengan SAK pada UMKM Alat Tulis : Studi Empiris pada UMKM di Sekitar Universitas Dr. Soetomo Surabaya - Herny Ria Mandag; Dyahnesa Harul Puspitaningrum; Sri Rahayuningsih (Jurnal Mutiara Ilmu Akuntansi, 2025)
Financial statements are important documents that describe the financial condition of an organization during a certain period of time. The purpose of this study was to see how Financial Accounting Standards (SAK) are applied to the financial statements of stationery MSMEs at Dr. Soetomo University, Surabaya. This study was conducted through a qualitative descriptive approach and case studies. Data were collected from stationery MSME actors through observation, interviews, and documentation. The results of the study indicate that most MSMEs still use simple manual recording and are not fully in accordance with SAK. This study suggests that MSME actors be trained and assisted to prepare financial statements in accordance with SAK, which will increase transparency and accountability.